The Life Experience of Ethnic Madurese Women in Early Marriage: A Phenomenological Study - Bawono, Yudho; Retno Suminar, Dewi; Hendriani, Wiwin (Universitas Airlangga, 2023)
The aim of this study was to explore the life experiences of Madurese women who entered into early marriages. Employing a qualitative research methodology with a phenomenological approach, the study encompassed nine Madurese women residing in Bangkalan, Sampang, Pamekasan, and Sumenep districts as participants. Semi-structured interviews were conducted for data collection. Additionally, in this phenomenological study, Interpretative Phenomenological Analysis (IPA) was employed for analysis. Through the data examination, eleven superordinate themes emerged, coalescing into four main themes. The findings of the study illuminated that the experience of early marriage among Madurese women was a dynamic process shaped by various facets of their lives. This encompassed deeply ingrained cultural beliefs, perspectives on marriage, the presence of arranged matches, and strategies for managing conflicts within their marital unions.